Spontaneous Activity of CB2 Receptors Attenuates Stress-Induced Behavioral and Neuroplastic Deficits in Male Mice - Ribeiro, Melissa A.; Aguiar, Rafael P.; Scarante, Franciele F.; Fusse, Eduardo J.; de Oliveira, Rubia M. W.; Guimaraes, Francisco S.; Campos, Alline C (Frontiers in Pharmacology, 2022)
The monoaminergic theory of depression/anxiety disorders cannot fully explain the behavioral and neuroplastic changes observed after ADs chronic treatment. Endocannabinoid system, which comprises CB2 receptors, has been associated with the chronic effects of these drugs, especially in stressed mice. CB2-KO mice display more vulnerability to stressful stimuli. In the present study, we hypothesized that the behavioral and neuroplastic effects observed after repeated treatment with the AD escitalopram (Esc) in chronically stressed mice depend on CB2 receptor signaling. Male mice submitted to chronic unpredictable stress (CUS) paradigm (21 days) were treated daily with AM630 (0.01; 0.03 or 0.3mg/Kg, i.p) a CB2 receptor antagonist/inverse agonist. At e 19th day of the CUS protocol, mice were submitted to Open field test and Tail-suspension test to evaluate antidepressant-like behavior. At the end of the stress protocol, mice were submitted to Novel Suppressed Feeding test ( day 22nd ) to evaluate anxiety-like behavior. In a second series of experiments, male mice treated with Esc (10mg/kg, daily, 21 days) in the presence or not of AM630 (0.30mg/Kg) were submitted to the same round of behavioral tests in the same conditions as performed in the dose-response curve protocol. Animals were then euthanized under deep anesthesia, and their brains/hippocampi removed for immunohistochemistry (Doublecortin-DCX) or Western Blot assay. Our results demonstrated that chronic treatment with AM630, a CB2 antagonist/inverse agonist, induces anxiolytic-like effects in stressed mice. Moreover, chronic reduction of CB2 receptor endogenous activity by AM630 attenuated the neuroplastic (potentiating stress-induced decreased expression of pro-BDNF, but enhanced pmTOR and DAGL expression in the hippocampus reduced in stressed mice), the antidepressant- but not the anxiolytic-like effects of Esc. AM630 alone or in combination with Esc decreased the expression of DCX+ cell in both the subgranular and granular layers of the dentate gyrus (DG), indicating a general reduction of DCX+ neuroblasts and a decrease in their migration through the DG layers. We suggest that the antidepressant-like behavior and the pro-neurogenic effect, but not the anxiolytic like behavior, promoted by Esc in stressed mice are, at least in part, mediated by CB2 receptors.